The dual loop model: its relation to language and other modalities - Rijntjes, Michel; Weiller, Cornelius; Bormann, Tobias; Musso, Mariachristina (Frontiers in Evolutionary Neuroscience, 2012)
The current neurobiological consensus of a general dual-loop system scaffolding human and primate brains gives evidence that the dorsal and ventral connections subserve similar functions, independent of the modality and species. However, most current commentators agree that, although bees dance and chimpanzees grunt, these systems of communication differ qualitatively from human language. So why is language in humans unique? We discuss anatomical differences between humans and other animals, the meaning of lesion studies in patients, the role of inner speech, and compare functional imaging studies in language with other modalities in respect to the dual loop model. These aspects might be helpful for understanding what kind of biological system the language faculty is, and how it relates to other systems in our own species and others.